2018
DOI: 10.1186/s13054-018-2005-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nighttime Rapid Response Team activation on outcomes of hospitalized patients with acute deterioration

Abstract: BackgroundRapid Response Teams (RRTs) are groups of healthcare providers that are used by many hospitals to respond to acutely deteriorating patients admitted to the wards. We sought to identify outcomes of patients assessed by RRTs outside standard working hours.MethodsWe used a prospectively collected registry from two hospitals within a single tertiary care-level hospital system between May 1, 2012, and May 31, 2016. Patient information, outcomes, and RRT activation information were stored in the hospital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
(48 reference statements)
2
29
1
1
Order By: Relevance
“…with daytime activation, which is in conflict with previous studies [21,22]. This may be attributable to the difference in the activation method of the MET: while the MET was activated only by calling from the ward staff in those studies, MET activation in our study was based on electronic medical record-based screening as well as calling.…”
Section: Plos Onecontrasting
confidence: 82%
“…with daytime activation, which is in conflict with previous studies [21,22]. This may be attributable to the difference in the activation method of the MET: while the MET was activated only by calling from the ward staff in those studies, MET activation in our study was based on electronic medical record-based screening as well as calling.…”
Section: Plos Onecontrasting
confidence: 82%
“…We found that hematologic oncology inpatients who experience RRS activation had an in-hospital mortality rate of 41.9%, which is higher than mortality among other previously studied RRS populations, including the elderly [37], general oncology patients [41], and surgical patients [42] (36.2%, 33%, and 28.4%, respectively). In our database, in-hospital mortality among non-hematologic oncology RRS patients was 29.9% [43], suggesting markedly higher mortality among the hematologic oncology population, as expected. This suggests that the hematologic oncology population is uniquely vulnerable, which may be due to the risk of infection and treatment-related complications in these patients, as described earlier.…”
Section: Discussionsupporting
confidence: 67%
“…There are no electronic or manual screening tools used for early detection of deterioration on the hospital wards. We conducted a retrospective analysis of prospectively collected data from The Ottawa Hospital Data Warehouse, a health administrative database that has been used widely in previous research [ 12 15 ]. Data quality assessments were performed during development and are executed routinely as new data are included.…”
Section: Methodsmentioning
confidence: 99%